Forestry Building interior showing wooden walkway and large tree stump, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: A corner of the Forestry Building. Alaska-Yukon-Pacific Exposition. Seattle, Wash. 1909. Official Post Card. Printed on verso: Portland Post Card Co. Seattle, Washington and Portland, Oregon. No. X154. PH Coll 777 PPCC.154 (See also PH Coll 78.60) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number